2020
DOI: 10.3390/ijerph17124226
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge Regarding the Consumption of Dietary Fiber and Its Relation to Self-Reported Health Status in an Adult Arab Population: A Cross-Sectional Study

Abstract: The objective of this study was to examine the awareness, knowledge, and habits regarding dietary fiber intake and to analyze its relationship with self-reported health status among Saudi adults. A survey-based study using face-to-face interview was designed, and 1363 apparently healthy adult Saudi males and females participated. Most participants were females (81.2%), aged 25 and above (87.2%), and were educated at least up to the secondary level of education (80.8%). The majority of the participants were awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In another study, the majority of respondents (70.5%) were aware of the importance of dietary fiber for controlling obesity, but there was a disconnect in translating this knowledge into dietary practices due to the perception that fiber‐rich food is expensive and unpalatable. Respondents in that study with the highest fiber consumption had a lower prevalence of obesity ( p = 0.03) 41 …”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In another study, the majority of respondents (70.5%) were aware of the importance of dietary fiber for controlling obesity, but there was a disconnect in translating this knowledge into dietary practices due to the perception that fiber‐rich food is expensive and unpalatable. Respondents in that study with the highest fiber consumption had a lower prevalence of obesity ( p = 0.03) 41 …”
Section: Resultsmentioning
confidence: 76%
“…Dietary studies in SA also, in general, lack clarity and the ability to discriminate local practices and customs that may be particular drivers of weight gain. During the past three decades, SA has witnessed a major shift from its traditional diet to the Western diet, particularly high in animal fats and refined sugars 41,42 . SAWHS 2019 also identified insufficient intake of fruits and vegetables among 93% of participants 112 .…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that participants had poor knowledge and an elevated consumption of salt, good knowledge of added sugar health risks, yet an elevated intake of sweets and fast foods and a low consumption of F&V [ 52 , 53 , 54 ]. An assessment among Saudi adults prior to the HFS implementation related poor fiber intake to the expensive prices of fruits and vegetables, limited availability and dislike of their taste [ 55 ]. Through educational campaigns, the SFDA intended to address the availability of F&V in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Pulses are also a rich source of dietary fiber. The daily adult intake of fiber, recommended by the World Health Organization (WHO), should be between 20–40 g [ 15 , 16 ]. The Institute of Medicine of the National Academy of Sciences 2005 [ 17 ] specifies the recommendations at 14 g per 1000 calories consumed [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%